BIOLOGICAL AND PRODUCTIVE PROPERTIES OF SINGLE-HUMPED CAMELS - Tleumuratov A. K.; Kaliyev B. A. (Journals Park Publishing, 2024)
In this article, we describe the biological and productive properties of a donut camel.
Keywords: Camel breeding, productivity, items milking, lactation.